ANTIBACTERIAL ACTIVITY OF PROTEIN EXTRACTS OF SELECTED MULBERRY VARIETIES - A. C. MANJULA,; L. H. SHIVASHANKARAPPA,; SHUBHA, (The Bioscan, 2010)
Mulberry is a member of the family Moraceae belongs to the genus Morus. The leaves are used to feed silkworms. It is a rich source of proteins. The plant has also been found to possess therapeutic value for many diseases. Protein extracts of selected mulberry varieties viz., Morus indica, V1, and DD was examined against different pathogenic bacteria using cup diffusion method. The heat stable protein extracts of these varieties exhibited varying degrees of inhibitory activity against different bacteria viz., Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis. Among the 3 varieties tested V1 variety showed more significant antibacterial activity against Pseudomonas aeruginosa, Bacillus subtilis and Escherichia coli whereas DD was more effective against Staphylococcus aureus.